Meningkatkan Mutu Pendidikan Melalui Manajemen Peserta Didik - Bustanul Arifin (STAIFAS-Press, 2018)
This paper discusses the improvement of the quality of education through students is one component in the education system that is important, in the world of education students are the raw material in the process of transforming science. Learning is a variety of components that are interconnected with one another. These components include objectives, material, methods and evaluation. The four components of learning must be considered by the teacher in choosing or determining the approach and learning model. Chasing activities in their implementation recognize many terms to describe the way of teaching that will be done by the teacher. At present there are so many kinds of learning strategies or methods that aim to improve the quality of learning to be better.